A Semiotic Analysis of Toxic Relationship as Portrayed in Story of Kale: When Someone’s in Love - Odelia Yulita; Marlina Marlina; Yuniawati Kencanasari (Budapest International Research and Critics University, 2021)
There are obstacles that originated from the participants involved in the relationship and interfere with everyday life and well-being becoming toxic. Unfortunately, toxic behaviors from lovers are often perceived as a gesture of love due to their romanticization in movies. Story of Kale: When Someone’s in Love, nevertheless, depicts toxic relationship as destruction in a relationship. This research aimed at identifying the signs of toxic relationships in the movie and interpreting them with Barthes’s semiotic analysis; order of signification. The study used interpretivism paradigm due to researchers’ subjectivity with the signs’ interpretation and qualitative case study with purposive sampling collected from the movie. Communicating toxic relationships has become essential since most couples are not aware they are in a toxic relationship either as the agent or as the victim. Toxic relationships can get worse during the pandemic for some couples who live together may feel suffocated from being with each other all the time and couples who live apart may develop more trust issues. Most previous research had discovered toxic relationships as a result of the patriarchal system in society. This current research found that toxic relationships can also be rooted in a sense of inferiority.